The first thousand years: a global history of Christianity - Wilken, Robert Louis (Yale University Press, 2012)
"A narrative account of the history of Christianity from its beginning to the end of the first millennium. The principal theme is the slow drama of the building of a Christian civilization. A major theme is the mission of Christians among different peoples in many regions of the ancient world: Ethiopia, Nubia, Armenia, Georgia, Persia, central Asia, India, China as well as among the Germanic peoples of northern Europe and the Slavic peoples in the Balkans and Russia. The rise and spread of Islam is integral to the story"--